Mob1: defining cell polarity for proper cell division - Tavares, Alexandra (2013)
Mob1 is a component of both the mitotic exit network and Hippo pathway, being required for cytokinesis, control of cell proliferation and apoptosis. Cell division accuracy is crucial in maintaining cell ploidy and genomic stability and relies on the correct establishment of the cell division axis, which is under the control of the cell's environment and its intrinsic polarity. The ciliate Tetrahymena thermophila possesses a permanent anterior-posterior axis, left-right asymmetry and divides symmetrically. These unique features of Tetrahymena prompted us to investigate the role of Tetrahymena Mob1. Unexpectedly, we found that Mob1 accumulated in basal bodies at the posterior pole of the cell, and is the first molecular polarity marker so far described in Tetrahymena. In addition, Mob1 depletion caused the abnormal establishment of the cell division plane, providing clear evidence that Mob1 is important for its definition. Furthermore, cytokinesis was arrested and ciliogenesis delayed in Tetrahymena cells depleted of Mob1. This is the first evidence for an involvement of Mob1 in cilia biology. In conclusion, we show that Mob1 is an important cell polarity marker that is crucial for correct division plane placement, for cytokinesis completion and for normal cilia growth rates.